2018
DOI: 10.1155/2018/7375693
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anthelmintic Activity of Methanolic Extract from Caesalpinia coriaria J. Willd Fruits against Haemonchus contortus Eggs and Infective Larvae

Abstract: The aim of this study was to evaluate the in vitro lethal effect of a methanolic extract (ME) from Caesalpinia coriaria fruits against Haemonchus contortus eggs and infective larvae. The anthelmintic activity was assessed using the egg hatching inhibition assay (EHI) and the mortality test. The ME was assessed using five concentrations as follows: 6.15, 3.12, 1.56, and 0.78 mg/mL to eggs and 150, 100, 75, and 50 mg/mL to larvae, respectively. Ivermectin (5 mg/mL) was used as positive control and 4% methanol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Plant materials tested for their in vitro anthelmintic activity in the present study have been identified by local livestock raisers. In vitro techniques such as the AMA and EHIA are preferred to in vivo methods due to their low cost, simplicity, and rapid turnover [23]. Moreover, for in vitro studies, H. contortus is proved to be a good test worm because of its longer survival in PBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant materials tested for their in vitro anthelmintic activity in the present study have been identified by local livestock raisers. In vitro techniques such as the AMA and EHIA are preferred to in vivo methods due to their low cost, simplicity, and rapid turnover [23]. Moreover, for in vitro studies, H. contortus is proved to be a good test worm because of its longer survival in PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for in vitro studies, H. contortus is proved to be a good test worm because of its longer survival in PBS. This abomasal helminth has recently been used for in vitro studies by other workers [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The studies on flavonoid derivatives proved that flavonoids have antibacterial, anthelmintic, antiviral, anti-inflammatory, anti-allergic, and anticancer activities. Plant active compounds were proved to suppress H. contortus [28][29][30][31]. Badar et al [32] stated that the variation in anthelmintic sericea leaf extract and agrimol G component [37].…”
Section: Discussionmentioning
confidence: 99%
“…The C. coriaria material was collected in the Toroqui community (which belongs to Wayuu community) in the rural area of the municipality of Riohacha, La Guajira (11˚29ʼ51.7 "N & 072˚50ʼ03.0" W) approximately 142.91 m 2 , the area is classified as tropical dry forest (16). The plant sample consisted of 500 g of ripe fruits of C. coriaria, applying a standard technique (17). First, the fruits were dried in a shadow and crushed to pulverize.…”
Section: Methodsmentioning
confidence: 99%